Adipose-derived stem cell exosomes for treatment of dupilumab-related facial redness in patients with atopic dermatitis - Hye Sung Han; Young Gue Koh; Jun Ki Hong; Yoon Jin Roh; Seong Jun Seo; Kui Young Park (Taylor & Francis Group, 2023)
Background Dupilumab facial redness (DFR) is a side effect of dupilumab treatment that has only been recently reported. We previously reported on two patients with DFR who were successfully treated with a topical formulation containing human adipose tissue-derived mesenchymal stem cell-derived exosomes (ASCEs). Objectives The study aimed to evaluate the efficacy and safety of ASCEs in DFR. Participants and methods We performed 12-week prospective study at single center. Twenty adult atopic dermatitis patients diagnosed with DFR were enrolled. They were treated with a topical application of the exosome formulation every week for five consecutive weeks. Results After exosome treatment, both the average investigator global assessment score and clinical erythema assessment scale scores decreased. 19 patients (95%) were satisfied with the treatment. Compared to baseline, erythema index at week 4 were decreased by 31, 27, 13, and 25 units on the forehead, chin, right and left cheek respectively. The analysis of stratum corneum samples revealed the expression of IL-1α and human thymic stromal lymphopoietin was suppressed after exosome treatment, whereas filaggrin and vascular endothelial growth factor expression increased. Conclusions This study suggests topical formulation containing ASCEs can alleviate DFR by downregulating local inflammation and restoring skin barrier function.